A walk among the tombstones [videorecording (DVD)] - Frank, Scott, 1960-; Neeson, Liam; Stevens, Dan, 1982-; Harbour, David, 1975-; Block, Lawrence (Universal Studios Home Entertainment, 2015)
Matt Scudder is an ex-NYPD cop who now works as an unlicensed private investigator operating just outside the law. When Scudder agrees to help a heroin trafficker hunt down the men who kidnapped and then brutally murdered his wife, the PI learns that this is not the first time these men have committed this sort of twisted crime, nor will it be the last. Blurring the lines between right and wrong, Scudder races to track the deviants through the backstreets of New York City before they kill again.